Sequential Shadowing Implies Spectral Decomposition - Khan, Abdul; Das, Tarun; Das, Pramod (Topology Proceedings, 2022)
We study chain recurrence for finitely generated group actions on metric spaces under the presence of the shadowing property. We introduce the sequential shadowing property for such actions and prove that this property implies the spectral decomposition property if the phase space is compact.